A prevalência da obesidade e hipertensão em três unidades básicas de saúde de Ponta Grossa- PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Obesity became an epidemy over the last years and is a leading fator associated in the development of noncommunicable diseases, with cardiovascular disease among them. We did not found any study that had demonstrated the prevalence and its relationship of with obesity and hypertension in the Ponta Grossa city – PR. In order to obtain the prevalence of hypertension and obesity we gathered data from 3434 patientes in three different primary healthcare facilities (PHF) from Ponta Grossa- PR from years 2015 to 2021. We gatherered data from sex, weight, height, BMI and blood pressure from the pacientes, using Kolmogorov-Smirnov, “U” Mann-Whitney, chi square and logistic binarian regression (p< 0,05). We found values that represented a prevalence of 29,6% obese and 39,9% hypertensive men and 35,3% obese and 27,4% hypertensive women. The age range with the higher prevalence of hypertension was between 40 and 59 years (37,7%) and in the PHF Silas Sallen. There is a higher risk of developing hypertension in male population, between obese and in older patients. We concluded that the data represent a concerning primary health background which are close to the ones of Parana and Brazil.
Keywords: Doenças Cardiovasculares; Unidade Básica de Saúde; Saúde pública; Atenção primária; Política pública; Cardiovascular Disease; Primary Healthcare Facility; Public Health; Primary Attention; Public Policy; CNPQ::CIENCIAS DA SAUDE